Matlab-based Calculation Method for Partitioning a Free-form Surface into Regions - Van, Tuong Nguyen; Naprstkova, Natasa (Manufacturing Technology Journal, 2019)
A Matlab-based calculation method which can be used to partition a free-form surface into regions is presented in this paper. Based on surface curvatures and Freeman chain code technique, a free-form surface can be devided into convex, concave and saddle regions. A Matlab program containing some M-function and script files was developed to create the mathematical model of the free-form surface, calculate the surface properties, and find the points on the boundaries of the regions. Two surfaces were given as examples to show that the program runs well and output of the program was used to create the CAD (Computer Aided Design) model of the partitioned surface in Creo Parametric.
Keywords: Surface Partitioning; Free-form Surface; Matlab Programming; Surface Curvature